ANALISIS PARAMETER MIKROSTRUKTUR NANOPARTIKEL Mn1-xZnxFe2O4 BERDASARKAN POLA DIFRAKSI SINAR X - Indrayana, I Putu Tedy (JST (Jurnal Sains dan Teknologi), 2019)
The Mn-Zn Ferit is a magnetic material which has potential applications for data storage device, the inductor coil and catalysis. This material has unique electrical and optical properties. Their properties are microstructural dependent. In this work, we studied the microstructural parameters of Mn1-xZnxFe2O4 which x assigns the mole fraction of Mn2+ and Zn2+ (x = 0.6; 0.7 and 0.8). Samples were synthesized by using coprecipitation method and NaOH as a coprecipitant. Microstructural parameters were investigated based on X-ray diffraction pattern. The crystallite size and strain were determined by using Size-strain plot (SSP) method. The crystallite size of nanoparticles is in a range of 18.9 nm â€“ 24.8 nm, while the strain is in a range of 0.0012 â€“ 0.0099. The lattice parameter is in a range of 8.531Çº - 8.567Çº bigger than the values were calculated theoretically according to the theoretical cation distribution model. The cation distribution in crystal lattice takes important rule in determining the microstructural parameters of nanoparticles.Â